Enhanced ablative resistance of C/C composites with densified ZrB2-based ceramics by incorporation of Mo as interface layer. (October 2022) - Zou, Hailiang; Zhang, Jinyong; Zou, Ji; Ping, Hang; Wang, Weimin; Ren, Lin; Fu, Zhengyi; Zhang, Fan
Abstract: ZrB2 -ZrC-SiC-Mo-C/C (ZZS-Mo-C/C) composites with dense composite ceramic coating and excellent interfacial bonding are synthesised using reaction spark plasma sintering (RSPS). Furthermore, the densification process, interfacial bonding, ablative properties and underlying mechanism of ZZS-Mo-C/C composites are investigated. Before and after ablation, the composite exhibits excellent interfacial bonding, indicating that the presence of Mo-foil transition layer enables an optimal connection between ZZS and C/C. Additionally, SEM analysis reveals that the ZZS ceramics have a dense structure, thereby preventing oxygen from diffusing further into the matrix. And the ablation results indicate that ZZS-Mo-C/C exhibits superior oxidation resistance when exposed to an oxygen-acetylene flame. Highlights: ZZS-Mo-C/C composite with strong interfacial bonding was prepared. The dense ceramic layer can fully resist the oxygen erosion at high temperature. The ablation resistance of C/C is greatly improved combining ZZS-Mo coating.